Measurement Properties of the Persian Translated Version of Graves Orbitopathy Quality of Life Questionnaire: A Validation Study. (2nd January 2017) - Kashkouli, Mohsen Bahmani; Karimi, Nasser; Aghamirsalim, Mohamadreza; Abtahi, Mohammad Bagher; Nojomi, Marzieh; Shahrad-Bejestani, Hadi; Salehi, Masoud
ABSTRACT: Purpose : To determine the measurement properties of the Persian language version of the Graves orbitopathy quality of life questionnaire (GO-QOL). Methods : Following a systematic translation and cultural adaptation process, 141 consecutive unselected thyroid eye disease (TED) patients answered the Persian GO-QOL and underwent complete ophthalmic examination. The questionnaire was again completed by 60 patients on the second visit, 2–4 weeks later. Construct validity (cross-cultural validity, structural validity and hypotheses testing), reliability (internal consistency and test-retest reliability), and floor and ceiling effects of the Persian version of the GO-QOL were evaluated. Furthermore, Rasch analysis was used to assess its psychometric properties. Results : Cross-cultural validity was established by back-translation techniques, committee review and pretesting techniques. Bi-dimensionality of the questionnaire was confirmed by factor analysis. Construct validity was also supported through confirmation of 6 out of 8 predefined hypotheses. Cronbach's α and intraclass correlation coefficient (ICC) were 0.650 and 0.859 for visual functioning and 0.875 and 0.896 for appearance subscale, respectively. Mean quality of life (QOL) scores for visual functioning and appearance were 78.18 (standard deviation, SD, 21.57) and 56.25 (SD 26.87), respectively. Person reliabilities from the Rasch rating scale model for both visual functioning and appearance revealed an acceptable internal consistency for the Persian GO-QOL. Conclusion : The Persian GO-QOL questionnaire is a valid and reliable tool with good psychometric properties in evaluation of Persian-speaking patients with TED. Applying Rasch analysis to future versions of the GO-QOL is recommended in order to perform tests for linearity between the estimated item measures in different versions.